The Use of Scaffolding Technique in Teaching Writing Descriptive Text - Reski Pilu (Ethical Lingua: Journal of Language Teaching and Literature, 2015)
This study deals with enhancing students’ ability in writing descriptive text at the second semester of English students of Cokoaminoto Palopo University. This research is aimed to find out whether the use of scaffolding technique is effective in improving the students’ competence in writing descriptive text. The scope of the research is focused on scaffolding technique in improving writing descriptive text ability of students. The research used pre-experimental method. Population is the second year students of English Students of Cokroaminoto Palopo, the number of population are 240 students. It used random sampling method. The members of sample were 25 students. The research instrument were used collect data, namely descriptive writing (written test). There is significance difference before and after using scaffolding technique as a treatment. The researcher concluded that scaffolding technique is effective in teaching writing to the students because it can improve the students’ writing competence. The researcher applied t-test analysis. The result of data analysis shows that there is significant difference between the pre-test and the post-test. The researcher concluded that using of scaffolding technique is effective in teaching writing descriptive text to the students at the second year of English students of Cokroaminoto Palopo University.